Forging power coalition politics in India - Chakrabarty, Bidyut, 1958- (New Delhi ; Oxford : Oxford University Press, 2006)
Presenting a study of coalition politics in India, this book argues that there has been a significant change from the post-independence one-party dominated polity. It also examines why coalition politics has become a dominant feature through renewed emphasis on questions of identity, dominant ideological dispositions, and regional preferences.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Political parties -- India; Coalition governments -- India; India -- Politics and government -- 1947-